2010
DOI: 10.1097/cad.0b013e32833db89d
|View full text |Cite
|
Sign up to set email alerts
|

Statistical identification of predictors for peripheral neuropathy associated with administration of bortezomib, taxanes, oxaliplatin or vincristine using ordered logistic regression analysis

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a major drug-induced adverse reaction that becomes a dose-limiting toxicity. However, effective strategies for preventing or treating CIPN are lacking. Accordingly, this study aimed to statistically identify predictors for CIPN. Retrospective analysis was carried out for 190 patients who had been treated with bortezomib (n=28), taxanes (paclitaxel or docetaxel; n=58), oxaliplatin (n=52) or vincristine (n=52) at our hospital between April 2005 and December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 24 publications
5
44
3
Order By: Relevance
“…An experimental study with rats has shown by electronic microscopy, that there were no significant pathological changes in the morphology of myelin sheath of animals treated with cisplatin, bortezomib and paclitaxel, although there has been decreased nervous conduction velocity 12 . There are evidences that platinum derivatives and taxanes would induce blood vessels endothelial cells apoptosis, with consequent nervous fibers ischemia 13 . Among pathophysiological CIPN mechanisms, it is currently recognized the role of neuroimmune interaction, since the release of cytokines and chemokines able to trigger peripheral neural injury seems to be a primary mechanism for the development of the syndrome.…”
Section: Pathophysiology Of Chemotherapy-indu-ced Peripheral Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study with rats has shown by electronic microscopy, that there were no significant pathological changes in the morphology of myelin sheath of animals treated with cisplatin, bortezomib and paclitaxel, although there has been decreased nervous conduction velocity 12 . There are evidences that platinum derivatives and taxanes would induce blood vessels endothelial cells apoptosis, with consequent nervous fibers ischemia 13 . Among pathophysiological CIPN mechanisms, it is currently recognized the role of neuroimmune interaction, since the release of cytokines and chemokines able to trigger peripheral neural injury seems to be a primary mechanism for the development of the syndrome.…”
Section: Pathophysiology Of Chemotherapy-indu-ced Peripheral Neuropathymentioning
confidence: 99%
“…CIPN incidence and severity are directly related to dose, number of treatment cycles, previous or simultaneous administration of neurotoxic anticancer agents and the type of impaired nervous fiber 13,18 . For example, when cisplatin is used alone, the frequency of neuropathic symptoms is around 50%, while 90 to 100% of females receiving the association of cisplatin and paclitaxel for ovarian cancer may present such symptom.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Reducing the dosage of bortezomib and/or changing the treatment schedule are also reportedly effective in alleviating bortezomib-induced PN (Argyriou et al, 2008a). However, neither the number of chemotherapy cycles nor the diagnosis of DM predicted bortezomib-induced PN (Kanbayashi et al, 2010). Additionally, since the use of thalidomide is not covered by the health insurance system in Japan, few patients (1 of 28 patients treated with bortezomib) received thalidomide co-administration (Kanbayashi et al, 2010).…”
Section: Bortezomibmentioning
confidence: 99%
“…However, neither the number of chemotherapy cycles nor the diagnosis of DM predicted bortezomib-induced PN (Kanbayashi et al, 2010). Additionally, since the use of thalidomide is not covered by the health insurance system in Japan, few patients (1 of 28 patients treated with bortezomib) received thalidomide co-administration (Kanbayashi et al, 2010). Thus, we did not include thalidomide in our analysis.…”
Section: Bortezomibmentioning
confidence: 99%
See 1 more Smart Citation